Kinetics and Thermodynamics of Adsorption Process Using A Spent-FCC Catalyst - Hussain, Zakir; Kumar, Rakesh; Meghavathu, Deepa (International Journal of Engineering and Technology, 2018)
Adsorption is potentially an attractive technique for the treatment of wastewater containing dyes. In the present work, spent fluid catalytic cracking catalyst (SFCC), a petroleum refinery waste was explored as a novel adsorbent and report its adsorption capability for the first time in the literature. Batch adsorption studies were carried out to remove methylene blue (MB) dye using SFCC. The equilibrium data was modeled using pseudo-first-order, pseudo-second-order, Elovich and intraparticle diffusion models. Also, the vanâ€™t Hoff equation was used to obtain the thermodynamic contributions of the process. Results show that the plot of intraparticle diffusion model (considering only film diffusion) has less R2 value (0.887); it seems that the plot is nonlinear. Hence, the data points were represented by a double linear set of equations (lines) considering both pore & film diffusion. In the first straight line, the sudden increase in slope signifies that the dye molecules were transported to the external surface of the adsorbent through film diffusion. The second straight line signifies that the dye molecules diffused through the pores. The portion which does not pass through the origin indicates that the pore diffusion is the only rate-determining step for the transport of MB onto SFCC.Â Â